Comparing Short-Duration Electro-Oculograms with and without Mydriasis in Healthy Subjects - Türksever, C.; Orgül, S.; Todorova, M. G. (Klinische Monatsblätter für Augenheilkunde, 2015)
Background: In order to obtain artifact-free electro-oculogram recordings the subjectʼs cooperation is necessary. The aim of our study is to evaluate the recording characteristics of short-duration EOG and to compare the effect of mydriasis on electro-oculogram recordings in a cohort of controls. Patients and Methods: Electro-oculogram recordings were performed on a light-emitting diode stimulus screen using a RETI-port gamma plus2 system (RETIscan™, Roland Consult). Fast oscillations were set at 1.5 sec (6 cycles; total duration 75 sec).The dark phase included: pre-adaptation (6 min), alternate fixation (4 min), fixation-rest (20 sec), 100 sweeps. The light phase included: light adaptation (4 min), alternate fixation (10 min), fixation-rest (20 sec), 250 sweeps. The amplifier band pass was filtered at 0.1 ÷ 50 Hz. The background illumination in mydriasis was 100 cd/m2 and in miosis – 450 cd/m2. Results: A total of 55 controls participated and were divided into three age groups [number; mean (years, y); ± SD]: group 1: 18–20 years (19; 19.49 years; ± 0.89); group 2: 20–40 years (18; 27.91 years; ± 5.39) and group 3: 40–60 years (18; 48.66 years; ± 4.00). The Arden ratio, dark-trough and light-peak did not differ between recordings with or without mydriasis (p = 0.914; p = 0.880; p = 0.680, linear mixed-effects model). The age did not influence the Arden ratio, dark-trough, light-peak (p = 0.206; p = 0.112; p = 0.155). Arden ratio, dark-trough, light-peak were comparable between tested eyes (p = 0.934; p = 0.193; p = 0.270). Conclusions: Short-duration electro-oculograms allow successful recording, furthermore, the application of mydriasis does not influence the quality of the recording.
Keywords: Arden-Quotient; ISCEV-Standard; Elektrooculogramm; Pigmentepithelium; Mydriase